Student Cognitive Engagement in High School Mathematics Classrooms of Nepal - Subedi, Sthir Babu; Shrestha, Shristi (Academic Journal of Mathematics Education, 2025)
In examination-driven education systems, student engagement often reflects strategic responses to assessment demands. Using a quantitative survey, this study examines the cognitive engagement strategies of 273 students of Grade 11 at an academically selective high school in Nepal, focusing on surface, deep, and teacher-reliant learning. Results show that students ideologically reject rote memorization as a superior approach, yet pragmatically employ memorization and repeated practice for academic success. Students report engagement in deep strategies, including self-questioning and seeking real-life applications, but show polarized responses in connecting new learning to prior knowledge. Strong reliance on teachers for content and problem-solving methods is evident. Gender differences were minimal, except that female students reported greater use of spare time for study. These findings demonstrate the influence of a high-stakes assessment culture on cognitive engagement in mathematics, underscoring the need for systemic reform in assessment and pedagogy.